2010
DOI: 10.1002/adsc.200900814
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Conjugate Addition of Carbonyl Compounds to Nitrodienes/Nitroenynes and Synthetic Applications

Abstract: The purpose of this study is to point out the synthetic utility of a new class of Michael acceptors (nitrodienes and nitroenynes). The highly enantioselective organocatalytic Michael addition of carbonyl compounds to these functionalized nitroolefins has been carried out in the presence of (S)-diphenylprolinol silyl ether to achieve some interesting building blocks in high selectivities. The adducts thus obtained can be easily converted by taking advantage of the corresponding unsaturated carbon-carbon bond. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(26 citation statements)
references
References 110 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…Among the numerous classes of alkyl moieties that can be successfully introduced in a catalytic and stereoselective fashion, propargyl chains are still somehow elusive. Among the limited number of existing protocols, representative asymmetric organocatalytic strategies have been reported by Krause, Alexakis, and co‐workers, who developed an aminocatalyzed conjugate addition of aldehydes to nitroenynes, whereas the group of Ma described the addition of ketones to the same class of Michael acceptors, using thiourea catalysis . These two protocols create a C−C bond at the α‐carbon of the starting carbonyl compound, in which the new branch installed carries both an alkynyl and a nitromethyl chain (Scheme a).…”
Section: Methodsmentioning
confidence: 99%
“…Among the numerous classes of alkyl moieties that can be successfully introduced in a catalytic and stereoselective fashion, propargyl chains are still somehow elusive. Among the limited number of existing protocols, representative asymmetric organocatalytic strategies have been reported by Krause, Alexakis, and co‐workers, who developed an aminocatalyzed conjugate addition of aldehydes to nitroenynes, whereas the group of Ma described the addition of ketones to the same class of Michael acceptors, using thiourea catalysis . These two protocols create a C−C bond at the α‐carbon of the starting carbonyl compound, in which the new branch installed carries both an alkynyl and a nitromethyl chain (Scheme a).…”
Section: Methodsmentioning
confidence: 99%
“…(), 16 O/ 18 O=40:60]. The amount of H 2 18 O used in the experiment was not described . As the isovaleraldehyde is difficult to monitor by mass spectroscopy, we selected {(4‐benzyloxy)cyclohexyl}acetaldehyde ( 1 ) as a β,β‐disubstituted aldehyde, which is easily monitored by mass spectroscopy, for the 16 O/ 18 O exchange experiment.…”
Section: Figurementioning
confidence: 98%
“…On the other hand, Alexakis reported that the Michael reaction of an aldehyde with nitrodiene, catalyzed by diphenylprolinol silyl ether, in H 2 18 O afforded mixture of 16 O‐aldehyde and 18 O‐aldehyde with the ratio 1:1.5 [Eq. ()] . Tsogoeva reported that a mixture of 16 O/ 18 O products (1:1.58) were obtained in the Mannich reaction of acetone with hydrazone, catalyzed by a primary amine thiourea [Eq.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…aldehydes and nitrodienes, [13] and Xu et al have shown the synergistic effect of an organocatalyst with a chiral thiourea for the reaction of cyclic ketones with nitrodienes. [14] However, the Michael addition of aromatic methyl ketones to nitrodienes is still a great challenge (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%